Neutron-induced light-ion production from Fe, Pb and U at 96 MeV - Stephan Pomp (2018)
Double-differential cross-sections for light-ion production (up to A = 4) induced by 96 MeV neutrons have been measured for Fe, Pb and U. The experiments have been performed at The Svedberg Laboratory in Uppsala, using two independent devices, MEDLEY and SCANDAL. The recorded data cover a wide angular range (20°-160°) with low energy thresholds. The data have been normalised to obtain cross-sections using np elastic scattering events. The latter have been recorded with the same setup, and results for this measurement are reported. The work was performed within the HINDAS collaboration with the primary aim of improving the database for three of the most important nuclei for incineration of nuclear waste with accelerator-driven systems. The obtained cross-section data are of particular interest for the understanding of the so-called pre-equilibrium stage in a nuclear reaction and will be compared with model calculations. © The Author 2007. Published by Oxford University Press. All rights reserved.